Nanorattles with tailored electric field enhancement - Schnepf, Max J.; Mayer, Martin; Kuttner, Christian; Tebbe, Moritz; Wolf, Daniel; Dulle, Martin; Altantzis, Thomas; Formanek, Petr; Foerster, Stephan; Bals, Sara; Koenig, Tobias A. F.; Fery, Andreas (Nanoscale, 2017)
Nanorattles are metallic core-shell particles with core and shell separated by a dielectric spacer. These nanorattles have been identified as a promising class of nanoparticles, due to their extraordinary high electric-field enhancement inside the cavity. Limiting factors are reproducibility and loss of axial symmetry owing to the movable metal core; movement of the core results in fluctuation of the nanocavity dimensions and commensurate variations in enhancement factor. We present a novel synthetic approach for the robust fixation of the central gold rod within a well-defined box, which results in an axisymmetric nanorattle. We determine the structure of the resulting axisymmetric nanorattles by advanced transmission electron microscopy (TEM) and small-angle X-ray scattering (SAXS). Optical absorption and scattering cross-sections obtained from UV-vis-NIR spectroscopy quantitatively agree with finite-difference time-domain (FDTD) simulations based on the structural model derived from SAXS. The predictions of high and homogenous field enhancement are evidenced by scanning TEM electron energy loss spectroscopy (STEM-EELS) measurement on single-particle level. Thus, comprehensive understanding of structural and optical properties is achieved for this class of nanoparticles, paving the way for photonic applications where a defined and robust unit cell is crucial.
CRIS-Team Scopus Importer:2022-04-14